1999
DOI: 10.1002/(sici)1097-0215(19990719)82:2<191::aid-ijc7>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of oral contraceptive use and risk of benign breast disease

Abstract: The purpose of the cohort study reported here was to investigate the association between oral contraceptive use and risk of benign breast disease (BBD), overall and by histological subtype, within the 56,537 women in the Cana-dian National Breast Screening Study (NBSS) who completed self-administered lifestyle and dietary questionnaires. The NBSS is a randomized controlled trial of screening for breast cancer in women aged 40-59 at recruitment. Cases were the 2,116 women in the dietary cohort who were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Thus, some studies have demonstrated protective action through their use, for example the studies by Canny et al 43 and Rohan and Miller, 44 while others found that oral contraceptives caused increased incidence of fi broadenoma, for example the study by Yu et al 45 We therefore put forward the theory that estriol, as a weak estrogen, may competitively block the stronger actions of the ethinyl estradiol present in oral contraceptives. This allows us to indirectly demonstrate that oral contraceptives have an important protective action in benign breast tumors, thereby resolving the doubts that persist in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, some studies have demonstrated protective action through their use, for example the studies by Canny et al 43 and Rohan and Miller, 44 while others found that oral contraceptives caused increased incidence of fi broadenoma, for example the study by Yu et al 45 We therefore put forward the theory that estriol, as a weak estrogen, may competitively block the stronger actions of the ethinyl estradiol present in oral contraceptives. This allows us to indirectly demonstrate that oral contraceptives have an important protective action in benign breast tumors, thereby resolving the doubts that persist in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…18,20 Our data further indicate that after cessation of OC use, ductal hyperplasia rapidly returns to a level intermediate between that of current users and never users.…”
Section: Discussionmentioning
confidence: 52%
“…[3], [4] Many demographic and social factors such as age, [5] , early marriage; socioeconomic status; menstrual status; oral contraceptives [6] ; shyness; reluctance for breast examination, etc. contributed to the pattern of disease and availability of material.…”
Section: Discussionmentioning
confidence: 99%
“…[6] In a case study of benign breast disease in Boston University in 1986, fibroadenoma was found to be the commonest benign tumour during 2 nd decade of life in married nullipara. [10] However, in our study, fibroadenoma was the 2 nd common benign breast disease [13.38%] with more probability on left side.…”
Section: Discussionmentioning
confidence: 99%